The relationships among love of money and unethical behaviour - Rahman, Farieza (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
This study examines the relationships between love of money and unethical behaviour, with Machiavellianism and narcissism, acted as the intervening variables. The data were collected by distributing a questionnaire to 122 banking employees in Yogyakarta and analysed using multiple regression analysis to test the hypothesis. Results indicate that Machiavellianism and narcissism were significantly related to unethical behaviour. Meanwhile, instead of love of money, which did not have any relationship with Machiavellianism, it had a significant relationship with narcissism. The implication of the findings is that a person who love for money and with high Machiavellianism are more likely to do unethical behaviour. However, people with high love of money are not always associated with a Machiavellianism personality.